Pengaturan dan Penegakan Hukum Pengupahan dalam Sistem Hukum Ketenagakerjaan - Zulkarnain Ibrahim (Jurnal Hukum IUS QUIA IUSTUM, 2015)
This research discusses the legal arrangement and enforcement of remuneration law in Employment Law (UUK) as an effort to realize the social welfare of workers. The method of this research was juridical empirical which regards law as a fact to observe and value-free. The research finding concludes that, first, UUD NRI (Indonesian Constitution) of 1945 has been weakened by UUK with its practice of labour market system and termination of employment. In addition, UUK has provided an opportunity for businessman to neglect his duty to respect the rights of Labour Union. Second, the enforcement of remuneration law is ineffective. Supevision from the Ministry of Manpower and Transmigration is hampered by the insufficient number of civil servant investigators (PPNS) compared to the number of companies.